Energetics of reactions between ceramic coating materials and their binary oxide components with silicate melts. Issue 12 (26th August 2022) - Costa, Gustavo; Harder, Bryan J.; Bansal, Narottam P.; Stokes, Jamesa L.; Lilova, Kristina; Subramani, Tamilarasan; Ushakov, Sergey V.; Meisner, Kevin J.; Navrotsky, Alexandra
Abstract: This paper summarizes our previous and current studies of using high‐temperature calorimetry to investigate the energetics of reactions of ceramic coating materials (e.g., yttrium disilicate and 7‐wt% yttria‐stabilized zirconia) and their binary oxide components with silicate melts in the CaO–MgO–Al2 O3 –SiO2 (CMAS) system. Such interactions are found to become stronger (more exothermic) with increasing difference in acid–base character between these materials and the melt. Our results suggest that the reactivity between the coating materials and the melt increases with decreasing thermodynamic stability (less exothermic enthalpy of formation from oxide components) of the coating material. They also suggest that ceramic coating materials made from binary oxides that have less exothermic enthalpies of solution and mixing are less susceptible to CMAS melt corrosion when in contact with an acidic, relatively polymerized, melt rich in SiO2 . Thus, we propose that new coating material formulation and CMAS melt corrosion mitigation strategies should be optimized based on the energetic contributions of their binary oxide components.